Inteligência artificial e responsabilidade penal - Ortiz, Mariana Fleming Soares (2023)
Artificial intelligence has never been closer to science fiction. With the advancement of technology, Law – as a regulator of human relations – has faced several challenges and questions in order to respond to the demands of society, especially in the criminal sphere. The present dissertation was developed from the study of doctrine, mainly international, in the search to understand the recent situation of the relationship between artificial intelligence and criminal law, passing through the analysis of concrete cases of violations of legal interests by machines, which have been occurring in world scope, as well as, by the analysis of the current regulations on the subject “artificial intelligence”. Finally, the focus is on tackling the issue from the perspective of the theory of crime, in terms of typicality, as a suggestion for tackling the problem. In summary, the objective of this dissertation is to discuss whether and how someone can be held responsible in Brazil for violations of legal interests caused by machines with autonomous systems and machines with self-learning.